Stereotactic radiosurgery for intracranial IgG4‐related disease. Issue 5 (1st August 2019) - Fogarty, Tamara; Choong, Dean; Gill, Suki; Harper, Chris; Robbins, Peter
Summary: We report the case of a 20‐year‐old woman with intracranial IgG4‐related disease, initially misdiagnosed as a meningioma on biopsy and treated with radiosurgery as it was in an eloquent location and not resectable. Her intracranial IgG4 disease had a near‐complete response to radiosurgery and is still controlled six years later, so this case represents what we believe to be the first reported use of radiotherapy in the treatment of intracranial IgG4‐related disease.